Crime, peoples and places: perspectives on rural safety and justice - Ceccato, Vania; Harkness, Alistair (Routledge studies in rural criminology, 2025)
"Building on previous work in rural criminology, this book casts a global and comparative look across nineteen countries, drawing on themes of crime and victimization, safety and fear, practices of policing and police trust, and crime prevention practices"--